PENGARUH KONSENTRASI SUKROSA TERHADAP KARAKTERISTIK PERMEN JELLY SIRSAK (Annona muricata Linn) - Teresina R.S. Simorangkir; Dekie Rawung; Judith Moningka (COCOS, 2017)
ABSTRACTSoursop fruit is a tropical plant that is well known by Indonesians. This is a fruit nutritious fruit plant, that is not only used as fresh food but can be processed into jelly candy. The aim of this study was to obtain an appropriate concentrations of sugar (sucroce) additions on the jelly candy processing based on, panelist responds on sensory dest of the jelly candy. The study was conducted using a completely randomized design with five treatments, including A (sucrose 20%), B (sucrose 25%), C (sucrose 30%), D (sucrose 35%), and E (sucrose 40%). The parameters analyzed were sensory, plasticity, moisture content, sucrose content, and vitamin C. The results showed that the C treatment (sucrose 30%) was the most favorable, on this treatment contains of 17.52% average moisture content, 44.51% average sucrose content, 21.90 mg/100 g average vitamin C content and 80.44 mm/g/s average plasticity content, respectively.Keywords: jelly candy, sucrose, soursop